University student participation in physical activity toward lung vital capacity differences: comparative study of smokers and non-smokers - Putra, Kukuh Pambuka; Al Ardha, Muchamad Arif; Tingsapat, Suthana; Wibowo, Cahyo; Sidi, Agam Allende (Bima Loka: Journal of Physical Education, 2025)
Smoking is a known risk factor for impaired lung function, even among physically active individuals. The harmful substances contained in cigarettes are known to disrupt lung function and damage lung tissue, which, over time, can reduce vital lung capacity. On the other hand, regular physical activity has been proven to enhance lung capacity. However, there is still a lack of research specifically comparing the vital lung capacity between physically active male smokers and non-smokers. This study aimed to determine the differences in vital lung capacity between physically active male smokers and non-smokers. The study involved 50 male university students aged 20–23 who regularly exercised twice weekly. Subjects were divided into 25 smokers and 25 non-smokers with similar morphological characteristics. Vital lung capacity was measured using a digital spirometer connected to a computer. The results showed that the non-smoker group had a significantly larger vital lung capacity than the smoker group, with an average difference of 0.41 liters (p<0.05). These findings indicate that although both groups were physically active, smoking habits still negatively impacted vital lung capacity. Although the difference may not be fatal from a physiological standpoint, it can potentially affect sports performance, particularly in disciplines that rely heavily on respiratory capacity, such as aerobic-based sports and freediving.